El desarrollo del artículo indefinido en español medieval y clásico - Pozas Loyo, Julia (El Colegio de México, 2012)
This paper offers a quantitative diachronic study of the developmentof Spanish un, from its cardinal value to its use as an indefinite article.Based on a corpus comprising texts from the thirteenth to theseventeenth century, I present an analysis and a chronology of themain changes undergone by un throughout this period, notably itsincreasing use as a marker of non-specific indefinites, and its furtherincorporation in generic noun phrases and predicates. Additionally,demonstrate that the development of the plural indefinite determinerunos is, with a few restrictions, parallel to that of its singularcounterpart, not only in its increasing frequency rate, but also in itsintroduction into new contexts.